Sequence analysis of 43‐year old samples of Plantago lanceolata show that Plantain virus X is synonymous with Actinidia virus X and is widely distributed. (20th November 2020) - Hammond, John; Adams, Ian P.; Fowkes, Aimee R.; McGreig, Sam; Botermans, Marleen; van Oorspronk, Joanieke J. A.; Westenberg, Marcel; Verbeek, Martin; Dullemans, Annette M.; Stijger, Christina C. M. M.; Blouin, Arnaud G.; Massart, Sebastien; et al.
Abstract: Plantain virus X was first recognized by the ICTV as a species in the genus Potexvirus in 1982. However, because no sequence was available for plantain virus X (PlVX), abolishing the species was proposed to the Flexiviridae working group of the ICTV in 2015. This initiated efforts to sequence the original isolates from Plantago lanceolata samples. Here we report the full‐genome sequencing of two original isolates of PlVX, which demonstrate that the virus is synonymous to Actinidia virus X, a species previously reported from kiwifruit ( Actinidia sp.) and blackcurrant ( Ribes nigrum ). PlVX was previously noted to be widespread in the UK in P . lanceolata . This report additionally presents novel data on the distribution and diversity of PlVX, collected at the same site as the original UK isolates, and from three independent surveys, two in the Netherlands and one in Belgium. This study also includes two new host records for PlVX, Browallia americana and Capsicum annuum (sweet pepper), indicating the virus is more widespread and infects a broader range of hosts than previously reported. This stresses the importance of surveys of noncultivated species to gain insight into viral distribution and host range. This study also demonstrates the value of generating sequence data for isolates retained in virus collections. Additionally, it demonstrates the potential value in prepublication data sharing for giving context to virus detections such as the four independent studies here which, when combined, give greater clarity to the identity, diversity, distribution, and host range of plantain virus X. Abstract : Historic and current samples of Plantago lanceolata infected with a potexvirus were sequenced demonstrating Plantain virus X is synonymous with Actinidia virus X and is widespread in the UK and Europe.